An Alternative Purification Method for Human Serum Paraoxonase 1 and Its Interactions With Sulfonamides - Ekinci, D.; Şentürk, M.; Beydemir, Ş.; Irfan Küfrevioǧlu, Ö.; Supuran, C.T. (Wiley-Blackwell, 2010)
Paraoxonase 1 (PON1), a high-density lipoprotein (HDL)-associated esterase, is known to mediate antioxidant and antiatherogenic properties. Purification of PON1 has been challenging for a long time. Here, we report a novel purification technique for this enzyme, which allowed us to obtain human serum paraoxonase 1 (hPON1) using straightforward chromatographic methods, such as Diethylaminoethyl-Sephadex anion exchange chromatography and Sepharose 4B-4-phenylazo-2-naphthaleneamine hydrophobic interaction chromatography. We purified the enzyme 302-fold with a final specific activity of 4775 U/mg and a yield of 32%. Furthermore, we examined the in vitro effects of some sulfonamide derivatives, such as sulfacetamide, homosulfanilamide (mafenide), sulfosalazine, furosemide, acetazolamide, and 1,3,4-thiadiazole-2-sulfonamide on the enzyme activity to better understand the inhibitory properties of the molecules. The six sulfonamides dose-dependently decreased the activity of hPON1 with inhibition constants in the millimolar - micromolar range. This study provides an efficient method, which may be useful for other enzymes such as those related to acetylcholinesterase. It also demonstrates the off-target activity of sulfonamides. © 2010 John Wiley & Sons A/S.
Keywords: Drug Target; Enzyme Purification; Inhibition; Paraoxonase; Sulfonamides